ANALISIS KEBERADAAN MINIMARKET INDOMART DAN ALFAMART TERHADAP OMZET PEDAGANG ECERAN DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - febri pratama; yurni suasti (JURNAL BUANA, 2020)
This research of aims; 1) knowing the turnover of retail traders in Tuah Karya village before and after the establishment of the minimarket 2) knowing the effect of the distance of the minimarket to the turnover of retail traders in Kelurahan Tuah Karya. This research is a descriptive quantitative research. The population of this research is all retail traders who have traded in Tuah Karya Village before and after the establishment of minimarkets and are in a radius of distance of ≤ 600 meters, the sampling technique in this study is total sampling, which is to take the entire population to be used as research samples. The results shows that: 1) there is a significant comparison of retail merchant turnover on several types of goods, such as rice, sugar, eggs and cooking oil. 2) there is the effect of distance on the turnover of the retail trader, which is the closer the distance between the minimarket and the retail trader, the influence received by the retail trader is greater and the further the distance between the retail trader and the minimarket, the effect received by the retail trader is getting smaller.